A Clinical Psychology-Based Psychoeducational Program to Enhance Happiness During Ramadan Fasting: A Quasi-Experimental Study Among Indonesian Muslim University Students - Yoza Okta Saputra; Tesa Dwi Surayana; RD. Devy Citra Pratiwi (IJIP : Indonesian Journal of Islamic Psychology, 2026)
First-year students experience a transitional phase from school to university. This phase often exposes them to various challenges, especially when observing the fast during Ramadan away from their families, giving rise to psychological dynamics such as fatigue, loneliness, and homesickness that can reduce students’ levels of happiness. Therefore, appropriate interventions are needed to help increase happiness. This study aimed to examine the effectiveness of the psychoeducational program ‘A Joyful Fast: A Clinical Psychology Perspective’ in enhancing happiness among first-year students. The study employed a quasi-experimental design using a one-group pretest–posttest approach. A total of 160 first-year students participated. Data were analyzed using the Wilcoxon signed-rank test. The results indicated an increase in happiness after the intervention, as evidenced by a significant difference between pretest and posttest scores (W = 2021, z = −7.26, p < .001) with a large effect size (r = 0.67). These findings suggest that the psychoeducational intervention is effective in increasing happiness among first-year students during Ramadan.